Risk assessment of flash – muddy flood and inundation of western Tam Dao mountainous region, Vinh Phuc province, Vietnam by using intergrated concept of hydrology and geomorphology - Thach, Nguyen Ngoc; Canh, Pham Xuan (VNU Journal of Science: Earth and Environmental Sciences; Vol 28 No 1, 2012)
Abstract. Flash flood, muddy flood and inundation are three phenomena of hydrological hazard. Normally, they are logically appeared in a catchment. In some other cases at mountainous region, they are separately appeared. Studies on these phenomena are still incompleted. Case study from area ofVinhPhucProvince, an intermediate watershed of Ca Lo River, located inWesternTamDaoMountain which cover nearly all region of theVinhPhucProvince. The performance of the concept was evaluated using statistical hydrological and geomorphological methods to assess the capability of the model in simulating the phenomena of flash flood, muddy flood in sloping regions and inundation in low land of the study area. By using ArcGIS 9.3 software, vertical eroded, watershed and stream accumulation, land cover, wetness index, geomorphology, and rainfall data layers have been created from DEM, SPOT images, topographic maps, and statistical data. By overlaying these layers and then reclassifying the integrated layer, difference types of flood can be separated as muddy flood, flash flood along accumulation network and inundation in low land. These results are useful date for regional planning of theVinhPhucProvince. Keywords: flash and muddy flood, inundation, sub-basin, hydrology, geomorphology, average slope value, integration.